PELAKSANAAN PELAYANAN ADMINISTRASI KEPENDUDUKAN MELALUI APLIKASI ONLINE DISDUKCAPIL DI KOTA PADANG - Disa Amalia; Aldri Frinaldi (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2024)
The Disdukcapil application is an innovation of population administration services that has been implemented by the Population and Civil Registration Office in Padang City. This application has been in place since March 30, 2020. This application aims to improve the quality of service to the community and be able to break the chain of the spread of Covid-19. The implementation of the Disdukcapil application is strongly influenced by the community's response. However, in fact, there are still many people who are not satisfied with this innovation. Therefore, research was raised on "Implementation Of Population Administration Services Through The Disdukcapil Online Application In Padang City, West Sumatera Province." The purpose of this study is to analyze, describe obstacles, and explain efforts to overcome existing obstacles. This study uses qualitative methods with an inductive approach, as well as data collection using observation techniques, interviews, documentation, trianggulation and data analysis using data reduction techniques. In Fact there are still many people who do not know the online application of Disdukcapil and many people also encountered people who come to the Office of Population and Civil Registration of Padang City to take care of population documents, as well as disruptions to the network and applications that are not perfect. So that for its improvement, regulations are needed related to the application for the creation of population documents in online applications, the need for socialization of online applications so that the public knows thoroughly, and periodic evaluation is needed by operators and district front offices so that services can be provided optimally